Large-Scale Screening in General Population Children for Celiac Disease with a Multiplex Electrochemiluminescence (ECL) Assay. (24th December 2020) - He, Ling; Jia, Xiaofan; Gu, Yong; Miao, Dongmei; Waugh, Kathleen; Geno, Cristy; Liu, Edwin; Rewers, Marian; Yu, Liping
Abstract : Background . Autoimmunity Screening for Kids (ASK) study was launched to screen general population children for type 1 diabetes (T1D) and celiac disease (CD). Methods . A total of 23, 319 children from general population were screened. A high throughput multiplex electrochemiluminescence (ECL) assay to screen multiautoantibodies in a single well was applied, parallel with a standard radiobinding assay (RBA). All children with any positive autoantibodies in screening were revisited within one month for confirmation and followed every 6 months. Results . Among 23, 319 children, 2.6% (606/23, 319) of children were tested positive for TGA. Multiplex ECL assay detected more TGA (584/23, 319) in the initial screening than RBA (490/23, 319, p = 0.004 ) and was able to detect TGA earlier than RBA in a subset of children by 0.8 to 34.8 months. Prevalence of TGA by either ECL or RBA in children with islet autoantibodies was found significantly higher than overall prevalence in general population screened. Conclusions . A multiplex ECL assay was more sensitive than standard RBA by identifying more TGA positivity and detecting TGA earlier in general population screening. It also provides a high efficient tool with its unique advantage of multiplexing measurements to screen for multiple autoimmune diseases simultaneously in general population.